128 Gbit/s Free-Space Laser Transmission Performance in a Simulated Atmosphere Channel With Adjusted Turbulence - Xianzhu Liu; Tianshu Wang; Xinmeng Zhang; Junda Chen; Peng Lin; Haifeng Yao; Juntong Zhan; Qiang Fu; Jinhua Yang; Huilin Jiang (IEEE Photonics Journal, 2018)
A 128 Gbit/s free-space laser link demonstration has been presented. We use a simulated atmosphere system with a tunable 1 km equivalent weak turbulence channel. Eye diagrams and constellation diagrams were observed. Bit error rate curves of back to back transmission and that in a simulated atmospheric channel are measured. The results show that the receiving sensitivities can be better than –37.3 dBm at the rate of 128 Gbit/s in a turbulence channel. To the best of our knowledge, it is the first time that the transmission performance of high speed space laser in a tunable atmospheric channel is studied.